2021
DOI: 10.1038/s41598-021-91819-7
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of bioelectrical impedance analysis and ECW ratio as a guidance for fluid management in critically ill patients after operation

Abstract: We determined the relationship between changes in bioelectrical impedance analysis (BIA) parameters and response of critically ill patients to fluid therapy during early postoperative period. Associations between BIA values indicating volume status of postoperative patient and clinical outcomes were also evaluated. From May 2019 to April 2020, patients who were admitted to the surgical intensive care unit (SICU) of our institution at more than 48 h after surgery were enrolled. Volume status was measured with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…75% of PE patients had excessive GWG [14]. The Da Silva study showed that TBW and ECW were higher in the group of women with PE, while in both absolute and relative terms the percentage of ICW was lower in this group [66,69].…”
Section: Gestational Hypertension and Preeclampsiamentioning
confidence: 87%
See 2 more Smart Citations
“…75% of PE patients had excessive GWG [14]. The Da Silva study showed that TBW and ECW were higher in the group of women with PE, while in both absolute and relative terms the percentage of ICW was lower in this group [66,69].…”
Section: Gestational Hypertension and Preeclampsiamentioning
confidence: 87%
“…The BIA method measures impedance, i.e., resistance value, caused by the h of intense exercise. The BIA method measures impedance, i.e., resistance value, caused by the difference in electrical conductivity of each type of biological tissue, e.g., fat or muscles [14]. The four-compartment model of body composition consists of the fat mass (FM) and the lean mass (FFM), which are further divided into the total body water (TBW), proteins and minerals (Figure 1) [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current methods used to evaluate uid status have limitations. Chung et al's [23] study showed that BIA and ECW/TBW ratios are useful and convenient tools used to assess the volume status of patients. According to the result of previous studies, the cut-off value for the assessment of edema was 0.39 [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Slobod et al's [27] study also showed that a higher ECW/TBW ratio within 24 h of admission was correlated with a longer duration of MV. Therefore, the ECW/TBW ratio can be a good prognostic factor for diseases or as a guide for uid management in critically ill patients [28,29]. BIA has intrinsic limitations in its ability to accurately distinguish between intravascular and interstitial volume in the extracellular compartment.…”
Section: Discussionmentioning
confidence: 99%